The Determination of The Acidity Constants and The Stability Constants of Flavokermesic Acid Complexes with Tin(II) and Aluminium(III) Ions by Potentiometric Method - AYAZ SEYHAN, SERAP (MARMARA UNIV, FAC PHARMACY, 2015)
Natural dyestuffs has been revived because of the fact that many of the synthetic dyestuffs are carcinogenic, toxic and their waste leads to environmental pollution. Thus, their usage has accelerated in the field of food, medicine, cosmetics and textile dyeing industry. Natural dyestuffs are soluble organic compounds obtained from plants, animals, lichens and fungi. The insect that have been and are still used today as sources of red textiles dyes, paint, pigment, food and pharmaceutical colorants are all classified in the super family Coccoidea of the class Homoptera. Flavokermesic acid (laccaic acid D) is a natural dyestuff obtained from this insect. In this study, the protonation constants of flavokermesic acid that acquired from kermes insect and the stability constants of complexes with metal ions were determined by potentiometric method.
Keywords: Dyestuff; flavokermesic acid; Kermes insect; potentiometri; acidity constant; QUERCETIN 3,3',4',5,7-PENTAHYDROXYFLAVONE COMPLEXES; MAGNESIUM(II); IRON(II)